Race to the future: Innovations in gifted and enrichment education in Asia, and implications for the United States - Kathryn C. Ibata-Arens (Administrative Sciences, 2012)
How are Asian countries preparing children to have skills-including creativity, innovation, and technical capability-to compete in the 21st Century global economy? Countries including China, Korea, Japan and Singapore have begun to integrate education policy and practice into a key component of national innovation strategies: human capital development. Asian countries are developing an emphasis on innovation and creativity at all levels of education, while the United States continues (via No Child Left Behind testing and budget cut-backs) to move away from that model. Developments in China (including Hong Kong and Taiwan), Korea and Singapore are complemented with comparisons to trends in national policy and private sector practice in Japan and the United States. Preliminary findings indicate that while progress has been made towards establishing education practices that enrich student learning, helping children to reach their highest potential in some countries, cultural practices and budgetary constraints have limited reform in others. The paper concludes with a summary of comparative best practices in enrichment education policy and practice and implications for globally competitive national innovation systems.
Keywords: 350; gifted education; GATE; Asia; China; Hong Kong; Japan; Korea; Taiwan; United States; innovation; talent; education policy; science education; enrichment education